2008
DOI: 10.1139/z08-057
|View full text |Cite
|
Sign up to set email alerts
|

Intersexual variation in the seasonal behaviour and depth distribution of a freshwater temperate fish, the largemouth bass

Abstract: Because fish are poikilothermic, water temperature is regarded as a primary factor influencing their activity and behaviour. Rarely have field studies been conducted with the spatiotemporal resolution to enable rigorous quantitative assessments of that relationship. Furthermore, there have been few studies that have considered the influence of sex on the seasonal behaviour of fish. Twenty largemouth bass (Micropterus salmoides (Lacepède, 1802)) were implanted with coded acoustic telemetry transmitters and remo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 58 publications
3
22
0
Order By: Relevance
“…swimming speed and distance travelled) have shown that largemouth bass typically increase activity during daylight periods, likely due to foraging and warmer temperatures relative to the nocturnal period (Demers et al, 1996;Hanson et al, 2007Hanson et al, , 2008Binder et al, 2012). More specifically, fish not exposed to elevated pCO 2 showed 37% and 36% decrease in MDT between 06:00-12:00:00 and 12:00:00-18:00 hours, respectively, whereas fish exposed to elevated pCO 2 did not have a discernible change in MDT.…”
Section: Discussionmentioning
confidence: 98%
“…swimming speed and distance travelled) have shown that largemouth bass typically increase activity during daylight periods, likely due to foraging and warmer temperatures relative to the nocturnal period (Demers et al, 1996;Hanson et al, 2007Hanson et al, , 2008Binder et al, 2012). More specifically, fish not exposed to elevated pCO 2 showed 37% and 36% decrease in MDT between 06:00-12:00:00 and 12:00:00-18:00 hours, respectively, whereas fish exposed to elevated pCO 2 did not have a discernible change in MDT.…”
Section: Discussionmentioning
confidence: 98%
“…Childs et al 2008;Cowley et al 2008;Hanson et al 2008;Heupel et al 2011). In an eastern part of Lake Ontario, for example, Hanson et al (2007) demonstrated that largemouth bass movements were positively correlated with water temperature.…”
Section: Discussionmentioning
confidence: 98%
“…Water temperature affects a number of life-history characteristics including metabolism, growth, migration and winter dormancy for largemouth bass (Hanson et al 2008). In particular, the initiation of spawning behaviour occurs with temperatures of 18 °C and greater (Cooke and Philipp 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Temperature, like DO, is a major determinant of fish distribution and behaviour (Carter, Weber, Dettmers, & Wahl, 2012;Hanson, Hasler, Cooke, Suski, & Philipp, 2008;Kramer & Smith, 1962). Temperature, like DO, is a major determinant of fish distribution and behaviour (Carter, Weber, Dettmers, & Wahl, 2012;Hanson, Hasler, Cooke, Suski, & Philipp, 2008;Kramer & Smith, 1962).…”
Section: Discussionmentioning
confidence: 99%